"Nasze filmy są w nas". Pomiędzy biografią a opowieścią o filmie (J. Kos-Krauze, A. Pawlicka, "Jest życie po końcu świata") = "Our films are in us". Between a biography and a tale about a film (J. Kos-Krauze, A. Pawlicka, "Jest życie po końcu świata") - Peroń, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
"Jest życie po końcu świata" by Joanna Kos-Krauze and Aleksandra Pawlicka consists of reportages, interviews and film reviews. Joanna Kos-Krauze and Krzysztof Krauze`s films, which make the backbone of the book, serve as a mirror which reflects their personal life. The stories of their film heroes reflect the problems of the world (genocide in Rwanda) but at the same time a private experience of the film maker (death of Krzysztof and Joanna?s mourning).
Keywords: correspondence of arts; film; reportage; memory; genocide; reportaż; pamięć; ludobójstwo